Recovery of Pt, Pd and Au from a cyanide solution through a carbon adsorption and elution process - Snyders, C.; Bradshaw, S.; Akdogan, G.; Mpinga, C.; Wyk, A.; Eksteen, Jacques (Gecamin, 2014)
In order to exploit lower grade and complex platinum group metal resources, cheaper and more efficient alternatives to the conventional mill-float-smelt-refine route are being sought, particularly for resources' in areas that are water-scarce and where electrification is costly and problematic. Leaching with cyanide is a promising process option and although recoveries are lower than in the conventional process routes, progress into the understanding of cyanide leaching of PGM containing ore and concentrate has been made. Research regarding the feasibility of upgrading the pregnant PGM leach solution using activated carbon has, however, been lacking and hence forms the focus of this paper. Bottle roll adsorption tests for dilute PGM solutions (0.15ppm Pt, 0.38 ppm Pd, 0.1 ppm Au) onto granular activated carbon showed high rates within the first 60 minutes (giving more than 90% recovery of precious metals). Comparison of the Pt isotherm to Au isotherms from literature indicated a similar loading capacity, while that of Pd was found to be significantly lower. The effects of solution pH, temperature, base metal concentration, free cyanide concentration, thiocyanate concentration, initial PGM concentration and activated carbon concentration were investigated and are discussed. Elution of the Pt and Pd, with the AARL elution process, was found to be effective with recoveries of 95% after 5 bed volumes of eluant at the optimum pre-treatment concentrations and a temperature of 80°C. Temperature, NaCN and NaOH pre-treatment concentration and the ionic strength of the eluant were found to be the most important factors affecting elution while base metals concentration, acid-pre-treatment, carbon loading and thiocyanate concentrations to a lesser extent. Simplified combined flow sheets are suggested and the corresponding mass balances are compared.